NLRP3 Deficiency Attenuates Renal Fibrosis and Ameliorates Mitochondrial Dysfunction in a Mouse Unilateral Ureteral Obstruction Model of Chronic Kidney Disease - Honglei Guo; Xiao Bi; Ping Zhou; Shijian Zhu; Wei Ding (Mediators of Inflammation)
Background and Aims. The nucleotide-binding domain and leucine-rich repeat containing PYD-3 (NLRP3) inflammasome has been implicated in the pathogenesis of chronic kidney disease (CKD); however, its exact role in glomerular injury and tubulointerstitial fibrosis is still undefined. The present study was performed to identify the function of NLRP3 in modulating renal injury and fibrosis and the potential involvement of mitochondrial dysfunction in the murine unilateral ureteral obstruction (UUO) model of CKD. Methods. Employing wild-type (WT) and NLRP3−/− mice with or without UUO, we evaluated renal structure, tissue injury, and mitochondrial ultrastructure, as well as expression of some vital molecules involved in the progression of fibrosis, apoptosis, inflammation, and mitochondrial dysfunction. Results. The severe glomerular injury and tubulointerstitial fibrosis induced in WT mice by UUO was markedly attenuated in NLRP3−/− mice as evidenced by blockade of extracellular matrix deposition, decreased cell apoptosis, and phenotypic alterations. Moreover, NLRP3 deletion reversed UUO-induced impairment of mitochondrial morphology and function. Conclusions. NLRP3 deletion ameliorates mitochondrial dysfunction and alleviates renal fibrosis in a murine UUO model of CKD.